Delayed hemolytic transfusion reaction with multiple alloantibody (Anti S, N, K) and a monospecific autoanti-JK(b) in intermediate β-thalassemia patient in Tabriz - Dolatkhah, Roya (Medknow Publications & Media Pvt Ltd, 2013)
It appears that delayed hemolytic transfusion reactions may occur several days after the administration of donor red cells is true even though they have been shown to be compatible in cross match tests by the antiglobulin technique. A specific case was observed in our center, which confirms the fact. The patient was a 37-year-old male suffering from intermediate β-thalassemia. He had a history of two previous transfusions, with unknown transfusion reaction. In the last transfusion, laboratory data showed: Hb 7.8 g/dL and Hematocrit (Hct) 24.2%. The patient received two units of cross matched, compatible concentrated red blood cells (RBCs). After eight days a severe reaction was observed with clinical evidence of tachycardia, fatigue, fever, back pain, chest discomfort, jaundice, nausea and anorexia. Accordingly delayed hemolytic transfusion reaction was suspected, and anti-RBC antibodies were tested. Laboratory tests revealed the presence of three alloantibodies: Anti-N, anti-S, anti-K, and a monospecific autoanti-JK(b).